Pengaruh Beban Kerja dan Stres Kerja terhadap Turnover Intention di Instansi Badan Penyelenggara Jaminan Produk Halal Kota Jakarta Timur - Rizka Wahyu Budiarti; Sugeng Prayetno (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to look at the impact of workload and work stress on employee turnover intentions at the Halal Product Assurance Agency (BPJPH). The method used is quantitative, and data is collected via questionnaires. A total of 50 BPJPH employees across multiple work units participated. Data were gathered through a questionnaire designed to quantify turnover intention, workload, and job stress. The data was analyzed with multiple linear regression to determine the association between work stress, workload, and employees' intention to quit the job. The results indicate that both work stress and workload significantly affect turnover intention at BPJPH, both partially and simultaneously. The combined impact of work stress and workload on turnover intention is 89.5%, while the rest is 10.5% is influenced by other variables not covered in this research. These findings highlight the importance of managing workload and work stress to reduce employees' intention to leave the organization, and provide insights for human resource management strategies at BPJPH.